The rhetoric of a political leader: from the ancient agora to electronic democracy - Vaičekauskienė, Giedrė (Information & Media, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]This article analyzes political leadership that uses rhetoric as one of the means to influence the electorate. Rhetoric denotes negotiatory communication between different individuals aimed at reaching a general agreement. This theoretical discourse reflects on the characteristics of classical rhetoric, established in the practice of citizenship of the Athenian Democracy, appealing to its return and identifying a new era of political communication – the characteristics of electronic democracy, which powerfully transforms the language and relations of the elected and representatives of the society. In a modern virtual agora, the political leader directly informs his electorate, and the internet provides the leader with a wide range of communication tools to influence the voter. The new media creates a new policy and a new political language, which becomes an object worthy of the researchers’ interest. The electronic agora is full of communicative noise, with the prevalence of a fragmentary, scattered, tag cloud rhetoric.The aim of this article is to reveal the issues of reliability of the rhetoric of the modern political leader from the perspective of political leadership constructed on the internet.
Keywords: political leader, political leadership, rhetoric, electronic democracy, political communication, deliberative democracy, personalization, populist style